ANALISA DAN PENDATAAN PENYEBARAN TENAGA TERDIDIK TIDAK PRODUKTIF MENGGUNAKAN SISTEM PEMETAAN WILAYAH ONLINE - Hidayatulah Himawan (Telematika, 2012)
Advances in technology are getting better can be used to manage and analyze theexistence of the spread of educated unproductive or unemployment in certain regions. Moreinformation system used to provide information about the status and presence and skill of eachperson, so hopefully with this system, managing and planning the handling modelunemployment will be better targeted. Information system developed using the model ofgeographic information systems (GIS). Mapping areas using GIS over the provision ofinformation to the spread of the data. The research method used is the waterfall model, wherethe system is planned and developed with the concept of handlers per area of any constraints.This research synergies between the variables that are used as analysis of population number,and the model needs and ordinances existing handlers.Keywords: information systems, GIS, Mapping Regional Analysis, Waterfall